ANALISIS RELIABILITAS KINERJA PEGAWAI KEMENTERIAN AGAMA KOTA BATAM DENGAN RASCH MODEL - Ph.D, Hazriyanto (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2019)
In generally, some problems that are often faced in how to create human resources capable of producing optimal performance so that organizational goals could be achieved. Some factors could be influenced a person's performance in an effort to achieve organizational performance. Performance measurement issues are important tobe focused. The variables examined in this research are items of performance instrument of employees at the office of the Ministry of Religion of Batam City. Data collection tools in the study using questionnaires and analyzed with winsteps rasch models. This assessment involves 6 performance instrument items. The population and sample in this study were 32 staff as respondents. Results of research shows that the reliability of an instrument item is in a good category. For future research, it is recommended to review items of reliability and other variables not examined in this study such as; emotional intelligence, commitment, and job satisfaction.